The theosis of the body of Christ : from the early British apostolics to a pentecostal trinitarian ecclesioloy - Black, Jonathan, Ph.D., (Global Pentecostal and Charismatic Studies;, 2020)
"In The Theosis of the Body of Christ: From the early British Apostolics to a Pentecostal Trinitarian Ecclesiology Jonathan Black builds on the ecclesiology of one of the UK's original Pentecostal movements, the Apostolic Church, demonstrating the connection between ecclesiology and the Pentecostal distinctive of the baptism in the Holy Spirit. These early British Pentecostals were not naïve fundamentalists with the addition of a few Pentecostal distinctives, but rather engaged in significant theological reflexion, rooted in Trinitarian theology, resulting in a theology of theosis which resonates in many ways with the Great Tradition, yet is held together with a forensic/Reformation approach to justification. This approach then opens new possibilities in understanding the theological nature of the Pentecostal baptism in the Spirit".